Are Stone Density and Location Useful Parameters That Can Determine the Endourological Surgical Technique for Kidney Stones That are Smaller than 2 cm? A Prospective Randomized Controlled Trial - Gucuk, Adnan; Yilmaz, Burak; Gucuk, Sebahat; Uyeturk, Ugur (Urology Journal, 2019)
Purpose: We aimed to evaluate whether these parameters could be guiding for us in selection between retrograde intrarenal surgery (RIRS) and mini-percutaneous nephrolithotomy (PNL) procedures in kidney stones that are smaller than 2 cm. Materials and Methods: The patients who had kidney stones smaller than two cm and were planned to undergo surgery were randomly distributed into 2 groups prospectively. RIRS was performed in the RIRS group using a 7.5-F fiberoptic flexible ureterorenoscope while mini-PNL group was dilated up to 16.5F and mini-PNL was performed with 12F nephroscopy. Preoperative characteristics, operative and postoperative results were compared in two groups. Thereafter, intra and intergroup comparisons were made to determine the effects of Hounsfield unit (HU) value indicating the stone density being higher or lower than 677 and stone location on stone-free rates. Results: The study involved 60 patients including 30 in each group. The groups’ preoperative values were similar. The hospitalization time and the total duration of scopy were longer in mini-PNL when the postoperative values were compared (P < .0001). In terms of stone densities, HU values that were lower than 677 in the mini-PNL group affected the stone-free rate and reduced it from 100% (> 677HU) to 55.6% (< 677HU), whereas the change was significant (P = .005). Lower calyx stones affected the RIRS results negatively, whereas multiple calyceal stones affected the mini-PNL group negatively. Conclusion: Both methods had a similar success rate, but lower pole stones, multiple calyceal stones and stone density parameters affected the stone-free rates significantly, and these may be effective in treatment selection.